Peter Handke's Kaspar: The Mechanics of Language—A Fractionating Schizophrenic Theatrical Event - Bettina L. Knapp (Studies in 20th & 21st Century Literature, 1990)
Theatre, for Handke, has neither object nor subject. concepts, values, functional systems of signification, verifiable contents are non existent in Kaspar. Words alone are of import; they alone create reality. Words, therefore, and not subjective evaluations of them, are acceptable to Handke, Comparisons, associations, metaphors, or references prevent people from dealing directly with the object itself (the signified), inviting them to have recourse to a "system of differences," to use Derrida's expression, thus contrasting or modifying one with the other. Evaluation breeds buffers and hierarchies; it encourages people to rank or compute ideas, notions, or feelings, and therefore prolong illusionism. Reality is not approached forthrightly, but rather experienced through a system of signs—a cultural product. This study aims at discovering Handke's innovative and challenging ideas concerning his manner of subverting conventional systems of relationships and comparisions. Words and figures of speech, as used in Kaspar, are mechanical devices endowed with concretion. Hard, unyielding, feelingless, these machine-like abstractions bludgeon into submission, cutting and dismantling well-worn responses to old ways of thinking and understanding. How the dramatist accomplishes his goals is analyzed.
Keywords: Peter Handke; object; subject; concepts; values; functional systems of signification; system; systems; verifiable contents; content; Kaspar; word; words; subjective evaluations; Comparisons; associations; metaphors; references; signified; signifier; system of differences; difference; differences; Derrida; contrasting; modifying; buffers; hierarchies; evaluation; rank; compute; ideas; idea; notion; notions; feeling; feelings; illusionism; signs; cultural product; experience; experienced; innovative; challenging ideas; manner; subverting; conventional; relationship; relationships; figures of speech; mechanical devices; concretion; dramatist; drama; play